Application of sewage sludge combined with thiourea improves the growth and yield attributes of wheat (Triticum aestivum L.) genotypes under arsenic-contaminated soil. - Nida Mansoora (Public Library of Science (PLoS), 2021)
Arsenic (As) contamination is a serious threat to agriculture and human health worldwide. It can adversely affect the growth attributes of food crops. On the other hand, using thiourea (TU) to ameliorate As stress is an economically consistent approach. However, there is a knowledge gap regarding the combined use of TU and Sewage sludge (SS). SS is considered important, unutilized biomass. It can be used as a fertilizer that has high organic matter and nutrients. Therefore, the current study was performed to evaluate TU and SS sole and combined responses under As toxicity on two wheat genotypes (Markaz 19 and Ujala 16). There were four treatments control (As 50 mg kg-1), SS (30 g kg-1)+TU (6.5 mM)+As, TU+As and SS+As applied with four replications. Results revealed that SS+TU performed significantly better over SS, TU and control for improvement in root and shoot fresh and dry weight of wheat varieties Markaz 19 and Ujala 16 under As toxicity. A significant decrease in POD, SOD and APX of Markaz 19 and Ujala 16 also validated the effective functioning of SS+TU over control. The maximum increase of 71 and 77% was noted in phosphorus, where SS+TU was applied over control in Markaz 19 and Ujala 16, respectively. In conclusion, SS+TU is a better approach than the sole application of SS and TU under As contamination for improvement in wheat growth attributes. More investigations are recommended at the field level under different As contamination and agro-climatic zones to declare SS+TU an effective amendment to mitigate As toxicity in wheat.